The Single-Case Reporting Guideline In BEhavioural Interventions (SCRIBE) 2016 Statement. Issue 7 (1st July 2016) - Tate, Robyn L.; Perdices, Michael; Rosenkoetter, Ulrike; Shadish, William; Vohra, Sunita; Barlow, David H.; Horner, Robert; Kazdin, Alan; Kratochwill, Thomas; McDonald, Skye; Sampson, Margaret; Shamseer, Larissa; et al.
Abstract : Abstract: We developed a reporting guideline to provide authors with guidance about what should be reported when writing a paper for publication in a scientific journal using a particular type of research design: the single-case experimental design. This report describes the methods used to develop the Single-Case Reporting guideline In BEhavioural interventions (SCRIBE) 2016. As a result of 2 online surveys and a 2-day meeting of experts, the SCRIBE 2016 checklist was developed, which is a set of 26 items that authors need to address when writing about single-case research. This article complements the more detailed SCRIBE 2016 Explanation and Elaboration article ( Tate et al., 2016 ) that provides a rationale for each of the items and examples of adequate reporting from the literature. Both these resources will assist authors to prepare reports of single-case research with clarity, completeness, accuracy, and transparency. They will also provide journal reviewers and editors with a practical checklist against which such reports may be critically evaluated. We recommend that the SCRIBE 2016 is used by authors preparing manuscripts describing single-case research for publication, as well as journal reviewers and editors who are evaluating such manuscripts. Scientific Abstract: Reporting guidelines, such as the Consolidated Standards of Reporting Trials (CONSORT) Statement, improve the reporting of research in the medical literature ( Turner et al., 2012 ). Many such guidelines exist and the CONSORT Extension to Nonpharmacological Trials ( Boutron et al., 2008 ) provides suitable guidance for reporting between-groups intervention studies in the behavioral sciences. The CONSORT Extension for N -of-1 Trials (CENT 2015) was developed for multiple crossover trials with single individuals in the medical sciences ( Shamseer et al., 2015 ; Vohra et al., 2015 ), but there is no reporting guideline in the CONSORT tradition for single-case research used in the behavioral sciences. We developed the Single-Case Reporting guideline In BEhavioural interventions (SCRIBE) 2016 to meet this need. This Statement article describes the methodology of the development of the SCRIBE 2016, along with the outcome of 2 Delphi surveys and a consensus meeting of experts. We present the resulting 26-item SCRIBE 2016 checklist. The article complements the more detailed SCRIBE 2016 Explanation and Elaboration article ( Tate et al., 2016 ) that provides a rationale for each of the items and examples of adequate reporting from the literature. Both these resources will assist authors to prepare reports of single-case research with clarity, completeness, accuracy, and transparency. They will also provide journal reviewers and editors with a practical checklist against which such reports may be critically evaluated. Keywords: single-case design, methodology, reporting guidelines, publication standards Supplemental materials: http://dx.doi.org/10.1037/arc0000026.supp